2004
DOI: 10.1080/10412905.2004.9698658
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the Essential Oil of a New Isomenthone-Rich Variant of Geranium Obtained from Geraniol-Rich Cultivar ofPelargoniumSpecies

Abstract: The hydrodistilled essential oil of the shoots of the geranium variant K-99 derived from the Pelargonium species 'Kunti,' a geraniol-rich cultivar that was found to be rich in isomenthone. The oil of this variant was found by GC and GC/MS analyses to have the major constituents menthone (2.7%), isomenthone (63.7%), decanoic acid (5.8%), 2-phenylethyl tiglate (2.1%) and 10-epi-γ-eudesmol (5.0%). The oil of the parent 'Kunti' contained linalool (5.1%), isomenthone (8.2%), citronellol (13%), geraniol (31.9%), ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…The overall magnitude of flux also grossly favored (−)-isomenthone production when the calculated rates of labeling were compared between the main end-products in each of the three chemotypes (1719 pmol 13 C mg −1 FW h −1 (−)-isomenthone in the (−)-isomenthone chemotype versus 218 and 70 pmol 13 C mg −1 FW h −1 (−)-citronellol and geraniol, respectively, in their respective chemotypes). Such a dominant role of the p -menthane pathway in determining product profiles would also be consistent with instances of spontaneous reversion of geraniol-rich cultivars to isomenthone-rich lines (Kulkarni et al , 1998; Gupta et al , 2001; Saxena et al , 2004). The identification of protein targets to overcome this natural tendency towards (−)-isomenthone production would be of value to breeders aiming to maximize geraniol and (−)-citronellol production, as well as their highly valued esters.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The overall magnitude of flux also grossly favored (−)-isomenthone production when the calculated rates of labeling were compared between the main end-products in each of the three chemotypes (1719 pmol 13 C mg −1 FW h −1 (−)-isomenthone in the (−)-isomenthone chemotype versus 218 and 70 pmol 13 C mg −1 FW h −1 (−)-citronellol and geraniol, respectively, in their respective chemotypes). Such a dominant role of the p -menthane pathway in determining product profiles would also be consistent with instances of spontaneous reversion of geraniol-rich cultivars to isomenthone-rich lines (Kulkarni et al , 1998; Gupta et al , 2001; Saxena et al , 2004). The identification of protein targets to overcome this natural tendency towards (−)-isomenthone production would be of value to breeders aiming to maximize geraniol and (−)-citronellol production, as well as their highly valued esters.…”
Section: Resultssupporting
confidence: 64%
“…However, a high C:G ratio also correlates with low night-time temperatures in the ‘Graveolens G1’ clone (Doimo et al , 1999). Interestingly, citronelloid dominant cultivars readily revert to a wild-type, isomenthone-rich phenotype as a result of somatic mutagenesis (Kulkarni et al , 1998; Gupta et al , 2001; Saxena et al , 2004). Thus, the C:G ratio in citronelloid-rich cultivated varieties is under environmental control while the prevailing structural group (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A somaclone, N75, obtained from internodal explants of the clone 'Narmada' treated with 0.25 mM NMU was found to contain a moderately high content of isomenthone (26-35%) in its essential oil. Although chemovariants with high contents of isomenthone (64-71%) have been reported in rose-scented geranium [3][4][5], somaclone N75, with a moderately high content of isomenthone, appeared to be new. Its essential oil composition with respect to 11 major and important constituents studied over two generations, SC 2 /VM 2 and SC 3 /VM 3 (second and third vegetative generations after in vitro phase mutagen treatment) is reported here.…”
mentioning
confidence: 84%
“…A wide range of monoterpenes, diterpenes and sesquiterpenes are generated through the action of terpene synthases/cyclases [8a]. Therefore, it may be assumed that these isomenthone-rich variants of Indian cultivars, 'Bourbon' and 'Kunti' [3][4][5] may have arisen through a mutation completely suppressing the conversion of GPP into alcohols (linalool, citronellol and geraniol) and their esters and leading to its conversion mainly into isomenthone. However, in the isomenthonerich somaclone reported by Gupta et al [4], the mutation probably did not completely suppress the conversion of GPP into alcohols, as the somaclone had 71% isomenthone and significant amounts of citronellol (6%), geraniol (3%), citronellyl formate (1.4%) and geranyl formate (0.5%).…”
mentioning
confidence: 99%
“…Geranium oil, an important product in perfumery, is processed from some hybrid species of Pelargonium and its world production reaches about 150 metric tons [2]. The essential oils of Geranium and Pelargonium species are widely used in the cosmetic and fragrance industry [3] and many studies on their composition have been reported [4][5][6][7].…”
mentioning
confidence: 99%